Experimental Study on the Effects of Freeze-Thaw Progressions and Performance of Soil with Non-Toxic Bio-Enzyme - Garzali Gali; Adnan Khan; Salman khan; Shahzad khalil; Qaim Shah; Murad Khan (Journal of ICT, Design, Engineering and Technological Science, 2023)
The Yakhtangay (Cold Valley) in District Shangla is encountering severe freeze-thaw cycles due to its elevated location and cold weather conditions. Repeated cycles of freeze-thaw action on soil cause it to lose strength, leading to settlement and a decrease in compressive strength. The objective of the study is to investigate the potential of terrazyme in enhancing the compressive strength of soil subjected to freeze and thawing cycles. Terrazyme, a bio enzyme obtained from plants and soluble in water, can reduce the water content from the soil while increasing inter-particle cohesion, leading to improved soil strength. The laboratory tests were conducted on both treated and untreated soil samples, and their properties were compared. The experimental study also included performing tests such as grain size distribution, Atterberg's limits, compaction, and compressive strength on the soil samples. Unconfined Compression Samples (UCS) were prepared and tested for freeze and thaw cycles in treated and untreated forms. The research utilized the optimal amount of Terrazyme, reducing water moisture content from 13% to 11%. Furthermore, using Terrazyme significantly increased soil compressive strength, with an improvement of 40%. Based on the study's results, terrazyme is proposed as a highly effective soil admixture that can significantly enhance soil properties—particularly its resistance against the negative impact of freeze-thaw cycles. This study can be implicated practically to avoid freeze-thaw problems in the soil of cold regions and can be proved fruitful for the researchers to study on the particular and related topics.